Learn Power BI a Comprehensive, Step-By-step Guide for Beginners to Learn Real-world Business Intelligence - Deckler, Greg (Packt Publishing, Limited, 2022)
Learn how to use Power BI to deliver the insights needed to help your enterprise survive and thrive Key Features Learn simple through to advanced Power BI features in a clear, concise way using real-world examples Develop powerful analytical models and reports that extract key business insights Publish, share and collaborate on impressive reports, dashboards, apps, and goals Book Description To succeed in today's transforming business world, organizations need business intelligence capabilities to make smarter decisions faster than ever before. This updated second edition of Learn Power BI takes you on a journey of data exploration and discovery, using Microsoft Power BI to ingest, cleanse, and organize data in order to unlock key business insights that can then be shared with others. This newly revised and expanded edition of Learn Power BI covers all of the latest features and interface changes and takes you through the fundamentals of business intelligence projects, how to deploy, adopt, and govern Power BI within your organization, and how to leverage your knowledge in the marketplace and broader ecosystem that is Power BI. As you progress, you will learn how to ingest, cleanse, and transform your data into stunning visualizations, reports, and dashboards that speak to business decision-makers. By the end of this Power BI book, you will be fully prepared to be the data analysis hero of your organization - or even start a new career as a business intelligence professional. What you will learn Get up and running quickly with Power BI Understand and plan your business intelligence projects Connect to and transform data using Power Query Create data models optimized for analysis and reporting Perform simple and complex DAX calculations to enhance analysis Discover business insights and create professional reports Collaborate via Power BI dashboards, apps, goals, and scorecards Deploy and govern Power BI, including using deployment pipelines Who this book is for If you're an IT manager, data analyst, or BI user new to using Power BI for solving business intelligence problems, this book is for you. You'll also find this book helpful if you want to migrate from other BI tools to create powerful and interactive dashboards. No experience of working with Power BI is expected.
Keywords: Microsoft Power BI (Computer file); Dashboards (Management information systems); Business intelligence -- Computer programs; Information visualization -- Computer programs; Tableaux de bord (Gestion); Visualisation de l'information; Logiciels; Information visualization; Computer programs